Chewing-stick practices using plants with anti-streptococcal activity in a Ugandan rural community - Okot Odongo, Charles; Odongo, Okot; Lubowa Musisi, Nathan; Waako, Paul; Obua, Celestino (Frontiers in pharmacology, 2011)
The high dental disease burden in developing countries has created a need to explore and develop cheap and accessible methods of dental disease prevention. Traditional toothbrushes (chewing-sticks) prepared from specific plants have been used for dental hygiene for generations. When properly used, chewing-sticks may be as effective as synthetic toothbrushes. This study set out to describe traditional chewing-stick practices in a Ugandan rural community, and evaluate the antibacterial activity of two most commonly used plants. Methods: Interviews were done to identify chewing-stick plants and obtain socio-cultural information relating to the practice in two villages in rural Uganda. Field walks were done to pick and voucher the plants, for taxonomical identification and storage. For the two most reported plants, aqueous extracts were prepared and tested for antibacterial activity against Streptococcus mutans using the agar-well diffusion method.
Keywords: Chewing-sticks; Rhus vulgaris; Lantana trifolia; Socio-cultural practices; Aqueous extract; Anti-streptococcal activity; Uganda